Engineering design : an introduction - Karsnitz, John R., 1945-; O'Brien, Stephen, 1959-; Hutchinson, John P. (Clifton Park, NY : Delmar Cengage Learning, 2013)
This book presents an overview of the basic engineering principles and concepts that shape today's modern world and includes activities and student explorations as learning tools.
pt. 1. The engineering design process -- pt. 2. Resources for engineering design.
"Project lead the way"- Cover.
Includes index.
Keywords: Engineering design